Geoinformatics Based Modelling of Channel Planform Dynamics for River Ramganga - Agnihotri, Ashwani Kumar (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Geoinformatics; Based Modelling of Channel Planform; Dynamics for River Ramganga